Thermodynamic mechanism of the high magnetic-field-induced morphology of ferrite. Issue 11 (24th July 2021) - Zhang, Dong; Hou, Tingping; Wu, Kaiming; Wang, Yu; Lin, Hengfu
Abstract : The stability of the ferrite morphology under a high magnetic field has been investigated according to the combination of the extended Weiss molecular field theory and the principle of minimum energy. The results showed that the ferromagnetic phase region decreases significantly with the increase of total angular momentum, whereas the paramagnetic phase region has the opposite tendency. The magnetic-field-induced morphology is noted to be closely related to the angular momentum, magnetic moment and interfacial energy. Based on the principle of minimum energy, the magnetic-field-induced aspect ratio (2.48:1) of the ferrite grains is in good agreement with the previous experimental data.